Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1073/pnas.0911073107
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic vesicle recycling by complex formation between intersectin 1 and the clathrin adaptor complex AP2

Abstract: Clathrin-mediated synaptic vesicle (SV) recycling involves the spatiotemporally controlled assembly of clathrin coat components at phosphatidylinositiol (4, 5)-bisphosphate [PI(4,5)P 2 ]-enriched membrane sites within the periactive zone. Such spatiotemporal control is needed to coordinate SV cargo sorting with clathrin/AP2 recruitment and to restrain membrane fission and synaptojanin-mediated uncoating until membrane deformation and clathrin coat assembly are completed. The molecular events underlying these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 23 publications
4
86
0
2
Order By: Relevance
“…For example, intersectin undergoes complex formation with early acting factors including FCHos 73 and EPS15, and with the sorting adaptors AP2 (REF. 71) and stonin 2 (FIG. 3c).…”
Section: Super-resolution Light Microscopic Techniquesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, intersectin undergoes complex formation with early acting factors including FCHos 73 and EPS15, and with the sorting adaptors AP2 (REF. 71) and stonin 2 (FIG. 3c).…”
Section: Super-resolution Light Microscopic Techniquesmentioning
confidence: 96%
“…Genetic studies have identified the multidomain endocytic scaffolding proteins intersectin [60][61][62]71 and epidermal growth factor receptor substrate 15 (EPS15) 72 as crucial for synaptic vesicle membrane retrieval and synapse development in Drosophila melanogaster and Caenorhabditis elegans. Expression levels of intersectin and EPS15 are interdependent, and the phenotypes observed on loss of either protein are nearly identical, indicating a close functional relationship between both proteins 72 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…On 6-8 days in vitro (DIV), neurons were transfected by calcium phosphate transfection (Promega Inc.). On DIV 12-15, neurons expressing synaptopHluorin or vGLUT1-pHluorin were live-imaged using a charge-coupled device camera (AxioCam; Carl Zeiss, Inc.) on an inverted microscope (Axiovert 200M; Carl Zeiss, Inc.) essentially as described previously (36,40 N-labeled synaptobrevin 2 were recorded on a Bruker DRX-600 NMR spectrometer in aqueous solution at 18°C, in complex with DPC at 30°C. Protein concentration was 0.5-1 mM in a buffer consisting of 150 mM NaCl, 5 mM DTT, 1 mM EDTA, 10% D2O, 20 mM Mes at pH 6.0, and optionally 200 mM DPC.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown recently that one mechanism of synaptojanin recruitment to the clathrin coat in neurons involves intersectin 1, and the binding of synaptojanin to intersectin is regulated by the adaptor protein complex AP2 (Pechstein et al, 2010). This allows for a possible synaptojanin-endophilin interaction, which is crucial for efficient uncoating of synaptic vesicles, to occur directly after fission, following disassembly of the endophilin-dynamin complex.…”
mentioning
confidence: 99%